PERLINDUNGAN HUKUM HAK CIPTA LAGU PADA INTERNET MENURUT UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Muh Jais (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractThis study aims to determine the legal protection provided by the government to copyright holders in overcoming acts of copyright infringement on the internet as well as to find out the task of investigating civil servants on copyrighted songs on the internet.This research is a field research assisted by library research, and uses a normative juridical approach that is holding fast to the norms, rules, and applicable provisions relating to the copyright of songs on the internet. Techniques used in collecting data include interviews with Parties Department of Justice and Human Rights of the Samarinda Region and the Department of Communication and Information Services of Samarinda City. Secondary data obtained through various sources such as books, journals, data from the internet and seminar papers which contained data needed in order to identify the data. systematically.Keywords : Copyright, Intellectual Property Rights